Implementation of Software-Based Accounting Information Systems in MSMEs and its Effect on Smoothness of Internal Audit (Food sector MSMEs in Langkat Regency) - Laily Ramadhani; Jung Sen; Adi Harianto; Tony Honkley; Vina Winda Sari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, including in Langkat Regency, where the food sector serves as a key economic pillar. A persistent challenge faced by these enterprises is the predominance of manual financial recordkeeping, which increases the risk of errors and complicates internal audits. This study aims to analyze the impact of software-based Accounting Information Systems (AIS) on the effectiveness of internal audits within food-sector MSMEs in Langkat Regency. The research employs an associative quantitative method, with a sample of 97 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings reveal that the implementation of software-based AIS has a positive and significant effect on the smooth execution of internal audits, as indicated by a t-statistic of 19.898 (greater than the critical value of 1.985) and a p-value of 0.000 (less than 0.05). Among the 95 valid respondents, 40% reported using accounting software and experiencing benefits such as improved accuracy in recordkeeping, timely financial reporting, and enhanced ease of internal auditing. The implications of this study underscore the importance of advancing digital accounting literacy, fostering local government support, and expanding access to affordable software solutions to strengthen transparency and competitiveness among food-sector MSMEs.